The role of leadership in empowering women in medicine - Aline Yacoubian; Nada Khaddage-Soboh; Jad Najdi; Albert El Hajj (Frontiers in Public Health)
Women continue to be understated and underestimated in leadership roles in science and medicine, where they face persistent gender bias and numerous challenges. This review paper seeks to detect the key barriers restricting female physicians’ access to leadership roles and to communicate key findings and recommendations from recent literature on gender equity in these disciplines. The review emphasizes substantial social barriers, including lack of support, mentorship, and sponsorship, alongside practical challenges such as excessive workload, childcare responsibilities, and limited career guidance, all of which deter leadership opportunities. The paper highlights the role of leadership in improving the visibility of female physicians and linking them to leadership opportunities. It also underlines the need for institutional funding through flexible work procedures, mentorship plans, and leadership enhancement plans, with the active participation of male leaders. The projected strategies aim to advance female physicians’ careers, challenge stereotypes about their leadership capabilities, and offer practical resources to enhance their representation in science and medicine—eventually fostering meaningful societal change.